Sosialisasi Digital Parenting: Pendekatan Orang Tua dalam Mendidik Anak di Era Digital - Novarossi, Gusti Dimas; Damayanti, Nina; Hairunnisa; Rabbani, Najwa Jembar Aulya; Afpriana, Mia; Yanti, Resti Safitri; Emilia, Rina; Andika, Arya Bhima; Maulana, Abdul Razak; Malindo, Andi Muhammad Alfian; Ilmi, Muhammad Fachrul; Hikmawan, Baso Didik; Junaidin; Ahmad, Islamudin (B-Creta Publisher, 2024)
The era of digitalization gives complete freedom to individuals, both parents and children, especially regarding access to all the information disseminated on social media. Of course, the number of gadgets is increasing among children, which has positive and negative effects. Therefore, this service activity aims to socialize digital parenting as a parental strategy to educate their children to use gadgets in a more targeted and time-bound way to reduce the negative impact of gadget use among children. The approach that will be taken is to provide learning or knowledge about the importance of understanding digital education, having the ability to use mobile phones, being critical of the media, and giving understanding through good delivery. At Mulawarman University's community service activities in Jenebora Village with the Digital Parenting Socialisation Work Programme, we delivered educational material about the importance of parents in educating children in today's digital age, which both parents and children attended. It is hoped that through this socialization, parents will increase their supervision of their children. Parents also hoped that this socialization in educating children in the digital era would be the first step in avoiding the harmful effects of mobile phone use on children.